Wisdom-based Thinking and Hexagonal Achievement Goal Approaches of Outstanding and Superior Students in the secondary stage in Makkah City - Alshehri, Shurog Ahmed; Hefny, Yasser Abdullah (Journal of Educational and Psychological Sciences, 2023)
The study aimed to learn the nature of the relationship between wisdom-based thinking and hexagonal achievement goal trends, as well as the differences as a result of the difference between type, specialization and predictability of hexagonal achievement goal trends, through wisdom-based thinking for high school students in Mecca. To achieve the study's objective, the interconnected descriptive survey curriculum was used. The tool was to build a gauge of wisdom-based thinking and use a gauge to guide the hexagonal achievement goal of the setup (Hassan, 2018) applied to a random caste sample of 248 superior students from some government high schools in Mecca. The study found several results, including Study sample students had a high degree of wisdom-based thinking and hexagonal achievement goal trends, and a statistically positive functional relationship between wisdom-based thinking and hexagonal achievement goal trends, and the study found that there was no statistically significant statistical impact of different disciplines. (Scientific-literary) and gender (male-female) in wisdom-based thinking and interactions, while there is a statistically significant influence between the sexes (male-female) in favour of males, and academic (scientific-literary) specialization in literary specialization, on trends and interactions between the six-party achievement goals. Trends in hexagonal achievement goals can be predicted through wisdom-based thinking and (sentencing) is the strongest indicator of goals (frequency/self), and the study recommends continuing weekly activities, in which students participate effectively, nurturing and supporting student achievements and excellence.
Keywords: wisdom-based thinking; achievement goal orientation; outstanding and superior scholastic students